Evaluation of Camelina (Camelina sativa L. Crantz Cv. Soheil) seeds storage during harvest to following growing season - Ali Shayanfar; Samad Mobasser; Bita Oskouei; Leila Zare (علوم و فناوری بذر ایران)
Camelina Cv. Soheil seed storability was assessed to simulate after-harvest condition till the following growing season. Seven seed samples were collected from Shirvan, Fasa, Marvdasht, Kermanshah, Hamedan, Sabzevar, and Ilam regions and saved for six months in two storage condition (with two temperatures of 10 and 25ºC). Then, they were drow out monthly from storage condition to evaluate different seed germination index and vigour. Moisture seed content did not acced more than 10 percent in all treatments. Germination percentage and normal seedlings were more than 94% after 6 months of storage in all seed samples and two temperatures. Weight seedling vigour showed no significant differences in all samples, except the Sabzevar sample. The effects of three factors (seed samples, temperature and storage time) on rate germination index were difference. Seed physiological responses (in terms of rate germination) to 10 and 25ºC temperatures were similar until the fourth months in more samples. However, a declining process was observed from the fourth month at 25ºC and from the fifth month at 10ºC for these responses and accend minimum in six months. Two seed samples of Hamedan and Kermanshah showed higher rate of germination. In total, Camelina seeds showed high storage potential due to high germination percentage was recorded after six months of storage. In addition, if seeds stored for more than 4 months, plants in field condition lower germination rate will observe.